Augmented Reality - Shakeel, Shazab Rehman; Shahbaz, Usman; Khan , Danish Shafeq (Advances in Social Sciences Research Journal, 2019)
In this paper describe the general ideal feature of Augmented Reality (AR) plus central conception of this type of technology. At this time it is also describe the major ground of AR and is also useful in that particular ground and tells about the very important AR devices. Future guidelines are also discussed and AR depended future technologies explain. A few uniqueness of Augmented Reality systems and devices will be talk about and this paper also will explain about AR overview.